Using of finite element method for solving problems of the resistance of materials - Pronkevich, S. A.; Senk, I. (БНТУ, 2007)
In this article we consider the using of finite element method for solving problems of the resistance of materials and compare results solved different methods: analytic solution, hand-calculation solution by finite element method and solution in ANSYS.